The impact of the COVID-19 pandemic on VET in the U.S. : interview - Farnbauer, Miriam [Interviewter]; Elliott, Diana [Interviewter]; Kress, Hannelore [Interviewer] (My University, 2022)
"In spite of the crises, apprenticeship models continue to develop, especially in the sector of information technology and communication. Cooperation between employers and community colleges remains a challenge for small and medium-sized businesses. Apprentices also need tutoring and coaching in per son in order to encourage and increase the finishing figures of the apprenticeship programms. Miriam Farnbauer and Dr. Diana Elliott reflect with GOVET team spokesperson, Dr. Hannelore Kress on these and other aspects in an interview." (Author's abstract; BIBB-Doku)
The impact of the COVID-19 pandemic on VET in the United States : interview
Keywords: I 2.3.2 Nordamerika; 370; Berufsausbildung; Pandemie; USA; Informationswirtschaft; Digitalkompetenz